Regional university as a center of science - Petr A. Savintsev (Высшее образование в России)
The author analyses the forms and mechanisms of the determination of the scientific research activity of a regional university functioning in the multicultural society (in the Kabardino-Balkar Republic as the example). The article reveals that in contemporary science and contemporary Russia most of the problems existing in the humanities that are traditionally referred (and refer) to the “local and insignificant” ones become urgent issues of national and global importance.